The Quality Analysis of Financing and Funding On the Performance of Bank Syariah Mandiri Jember Area of 2015 - 2019 - Wardhani, Roro; Apramada, Barid Paladin; Fadah, Isti; Sumani, (International Journal of Scientific Research and Management (IJSRM), 2020)
AbstractIn general, this study aims to analyze the Quality of Funding and Funding Against the Performance of Sharia Bank Mandiri in Jember Area for the Period 2015 - 2019. The population of this study is the quarterly financial statements of Bank Syariah Mandiri in Jember Area in 8 branches from 2015 to 2019. The sample is part of a population object that represents its population characteristics. The sampling design in this study was by means of the census method, namely the population being the study sample, so that collected 8 x 5 x 4 = 160 data analysis. Hypothesis testing uses multiple linear regression analysis test tools. After analyzing the data, several conclusions can be drawn, namely: the quality of current productive assets partially has a significant positive effect on the performance of Bank Syariah Mandiri in Jember Area, which is proxied by ROA, the quality of productive assets under special attention partially has a significant negative effect on the performance of Bank Syariah Mandiri in Jember Area , the quality of substandard productive assets partially has a significant negative effect on the performance of Bank Syariah Mandiri Area Jember, the quality of productive assets is doubtful partially has a significant negative effect on the performance of Bank Syariah Mandiri Area Jember, the quality of the non-productive assets partially has a significant negative effect on the performance of Bank Syariah Mandiri In Jember Area, funding proxied by DPK partially has a significant positive effect on performance. Keywords: financing quality, funding and performance